Signalling pathways in ischaemic postconditioning - Hausenloy, Derek J. (Thrombosis and Haemostasis, 2009)
Coronary heart disease (CHD) is the leading cause of death globally. Following an acute coronary artery occlusion, timely myocardial reperfusion using either primary percutaneous coronary intervention (PCI) or thrombolytic therapy remains the most effective treatment strategy for reducing myocardial infarct size, preventing left ventricular remodelling, preserving left ventricular systolic function and improving clinical outcomes. However, the full benefits of myocardial reperfusion are not realised, given that the actual process of reperfusing ischaemic myocardium can independently induce cell death – a phenomenon termed lethal reperfusion injury. Ischaemic postconditioning represents an innovative treatment strategy for limiting lethal myocardial reperfusion injury and further reducing myocardial infarct size for those patients undergoing primary PCI. It is achieved by interrupting the normal myocardial reperfusion process, with several intermittent episodes of coronary myocardial ischaemia induced by low-pressure inflations of the angioplasty balloon in the infarct-related coronary artery. Experimental studies demonstrate that this stuttered form of myocardial reperfusion improves myocardial perfusion, maintains endothelial function, attenuates apoptotic cell death, reduces myocardial infarct size, preserves left ventricular systolic function and reduces mortality. The mechanisms underlying the cardioprotective effect of ischaemic postconditioning are the subject of intense investigation. In this article we review the signalling pathways which have been implicated as potential mediators of ischaemic postconditioning, the identification of which have provided novel pharmacological targets of cardioprotection capable of recapitulating the protective benefits of ischaemic postconditioning.
Keywords: Reperfusion injury; ischaemic postconditioning; protein kinases; mitochondrial permeability transition pore; myocardial infarction